2013
DOI: 10.3390/ijerph110100202
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Metal Concentrations in Cigarettes Obtained from U.S. Smokers in 2009: Results from the International Tobacco Control (ITC) United States Survey Cohort

Abstract: Smoking-related diseases can be attributed to the inhalation of many different toxins, including heavy metals, which have a host of detrimental health effects. The current study reports the levels of arsenic (As), cadmium (Cd), chromium (Cr), nickel (Ni), and lead (Pb) in cigarettes obtained from adult smokers participating in the 2009 wave of the ITC United States Survey (N = 320). The mean As, Cd, Cr, Ni, and Pb levels were 0.17, 0.86, 2.35, 2.21, and 0.44 µg/g, respectively. There were some differences in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
1
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 41 publications
7
69
1
6
Order By: Relevance
“…Torjussen et al (2003) indicated that nickel content is high in cigarettes, and it was in the range of 6.2-50.5 μg/L in the blood plasma of smokers [29]. Also, a study on US adult smokers (2009) reported that the mean value of nickel levels in cigarettes was 2.21 ± 0.54 μg per gram of tobacco [17]. Therefore, mothers' exposure to tobacco smoke can be one of the ways of entering nickel into the breast milk.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Torjussen et al (2003) indicated that nickel content is high in cigarettes, and it was in the range of 6.2-50.5 μg/L in the blood plasma of smokers [29]. Also, a study on US adult smokers (2009) reported that the mean value of nickel levels in cigarettes was 2.21 ± 0.54 μg per gram of tobacco [17]. Therefore, mothers' exposure to tobacco smoke can be one of the ways of entering nickel into the breast milk.…”
Section: Discussionmentioning
confidence: 94%
“…Nickel toxicity studies on animals revealed the lipid peroxidation in the kidney, liver, and lung [17]. The data from human studies indicate that symptoms of acute exposure to nickel consist of gastro-intestinal disorders (nausea, vomiting, abdominal pain, and diarrhea), visual disturbance, headache, vertigo, and cough.…”
Section: Introductionmentioning
confidence: 96%
“…79 Cadmium has been shown to reduce CFTR expression via a miRNA dependent pathway, reducing channel function. Moreover, cadmium levels in lung were correlated with COPD disease severity independent of the duration of cigarette smoking.…”
Section: Mediators Of Cftr Dysfunction In Cigarette Smokementioning
confidence: 99%
“…Nickel concentrations in the air can reach high levels at industrial workplaces where it is used [4]. Additionally, nickel is present in cigarette smoke [5]. Inhalation exposure to nickel is associated with pulmonary inflammation, epithelial hyperplasia, fibrosis, asthma, and lung cancers [1,2,3].…”
Section: Introductionmentioning
confidence: 99%